Analysis of Latent Tuberculosis Risk Factors Detected by Tuberculin Skin Tests in Chronic Kidney Disease Patients Undergoing Routine Hemodialysis - Mardiansyah, Muhammad Andi; Arliny, Yunita; Yusuf, Nurrahmah; Abdullah, Abdullah (Jurnal Respirologi Indonesia, 2025)
Background: Due to changes in the immune system, chronic kidney disease (CKD) patients on routine hemodialysis (HD) are at increased risk for latent tuberculosis (LTB). Latent tuberculosis requires special attention to prevent its development into active form because infection increases mortality in CKD patients. This study aims to determine the prevalence and risk factors associated with LTB in CKD in routine HD patients. Method: This research uses a cross-sectional design and is an analytical observational study. The study was conducted in the Hemodialysis Unit at dr. Zainoel Abidin Hospital between June and August 2023, using consecutive non-probability sampling. Results: Of the 289 CKD patients undergoing routine hemodialysis, 54 met the inclusion criteria. The prevalence of latent tuberculosis among these patients was 27.8%, as determined by the Tuberculin Skin Test (TST). Statistical analysis revealed no significant association between LTB and risk factors such as age, gender, body mass index, smoking status, or CKD etiology (P>0.05). Due to value of P>0.25, multivariate analysis could not be performed. Conclusion: There is a high prevalence of latent tuberculosis among chronic kidney disease patients undergoing dialysis. The risk factors for LTB remain unclear. However, early diagnosis and treatment are recommended to prevent progression to active TB.